Discrepant responses of soil organic carbon dynamics to nitrogen addition in different layers: a case study in an agroecosystem - Hualing HU; Liang ZHAO; Wenbing TAN; Guoan WANG; Beidou XI (Frontiers of Agricultural Science and Engineering)
● 13C isotope analysis was used to estimate the contribution of new and old carbon to SOC. ● The maize plot with high N rate improved SOC fixation than the maize plot with low N rate. ● The maize plot with high N rate transferred organic matter to a deeper soil layer. ● There are remarkable differences in turnover time of SOC under different N rates. Empirical research indicates that heightened soil nitrogen availability can potentially diminish microbial decomposition of soil organic carbon (SOC). Nevertheless, the relationship between SOC turnover response to N addition and soil depth remains unclear. In this study, soils under varying N fertilizer application rates were sampled up to 100 cm deep to examine the contribution of both new and old carbon to SOC across different soil depths, using a coupled carbon and nitrogen isotopic approach. The SOC turnover time for the plot receiving low N addition (250 kg·ha−1·yr−1 N) was about 20−40 years. Conversely, the plot receiving high N (450 kg·ha−1·yr−1 N) had a longer SOC turnover time than the low N plot, reaching about 100 years in the upper 10−20 cm layer. The rise in SOC over the entire profile with low N addition primarily resulted from an increase in the upper soil (0−40 cm) whereas with high N addition, the increase was mainly from greater SOC in the deeper soil (40−100 cm). Throughout the entire soil layer, the proportion of new organic carbon derived from maize C4 plant sources was higher in plots treated with a low N rate than those treated with a high N rate. This implies that, in contrast to low N addition agricultural practices, high N addition predominantly enhances the soil potential for fixing SOC by transporting organic matter from surface soils to deeper layers characterized by more stable properties. This research offers a unique insight into the dynamics of deep carbon under increased N deposition, thereby aiding in the formulation of policies for soil carbon management.